Damage quantification in an AlSi10Mg cellular metamaterial using 4D measurements - Mandić, Ana; Kosin, Viktor; Smaniotto, Benjamin; Salvi, Laura; Gabriella Tarantino, M; Hild, François (Measurement science & technology, 2025)
Projection-enhanced digital volume correlation is applied for the 4D characterization of damage in an AlSi10Mg cellular metamaterial produced by laser powder bed fusion. The inspected specimen contained elliptical voids, which was subjected to in situ uniaxial tension and imaged via x-ray tomography. The focus of this study is to quantify damage growth by analyzing residuals directly from radiographs. In addition, damage mechanisms inducing specimen failure are studied.